PENGARUH ANALISA LAPORAN KEUANGAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI: Studi Empiris pada Perusahaan Bursa Efek Indonesia tahun 2018-2021 - I Gede Yuli Arta Sariyasa; I Made Marsa Arsana; Luh Gede Putri Kusuma Pekerti (Universitas Triatma Mulya, 2023)
This review expects to test and exhibit the meaning of the way that the liquidity (current proportion), capital power, stock force, influence (obligation to resource proportion), and benefit (return on resources) of organizations in the shopper products industry that are recorded on the Indonesia Stock Trade impact charge evasion. This study uses a quantitative; the general population in this study was 209 purchaser items industry associations recorded on the Indonesia Stock Exchange. The study covered a four-year period, from 2018 to 2021. A sample of 25 businesses was chosen using purposeful sampling based on a variety of factors. Methods of data analysis include the coefficient of determination test, the multiple linear regression test, the model feasibility test (F), and the classical assumption test. Companies in the consumer goods sector that do not pay taxes that are listed on the Indonesia Stock Exchange are unaffected by the variable liquidity, according to the study. The Capital Intensity variable makes it much less likely for companies in the Consumer Goods Industry that are listed on the Indonesia Stock Exchange to avoid paying taxes. On the Indonesia Stock Trade, tax avoidance by Buyer Merchandise Industry Organizations is unaffected by influence variable. The profitability variable has no effect on companies in the Consumer Goods Industry listed on the Indonesia Stock Exchange evading taxes. The variables Liquidity, Capital Intensity, Inventory Intensity, Leverage) and Profitability have an adjusted R square value of 0.114, indicating that they can explain 11.4% of tax avoidance, while other variables outside of this research model can explain the remaining 88.6%.